AI-Driven Financial Planning: The Future of Investment Advice Through Advanced Analytics - Mohammad Daffa' Almadani Sujarwo; Anak Agung Gde Satia Utama (Department of Accounting, Faculty of Economics & Business, 2025)
The development of technology today has experienced a fairly rapid development, especially in the field of Finance. There are also various technologies that experience these developments, one of which is artificial intelligence (artificial intelligence). According to the literature study, the role of AI can help investors in making investment decisions and financial planning efficiently and effectively. The purpose of writing is to analyze how AI Analysis helps investors in investment decision and financial planning. The research methods used in this writing adopt qualitative research methods. The results of the study describe the application of The Theory of Planned Behavior has several components including attitude toward the behavior, subjective norms, and perceived behavioral control. AI algorithms can help identify deeper patterns of behavior in credit and investment decision making, thereby improving the accuracy of predictions and recommendations given to investors or lenders. The conclusion is that AI analysis can help investors to make well-planned and confident investment decisions. In addition, through the existence of AI can also improve the effectiveness of financial planning and reduce uncertainty. Based on The Theory of Planned Behavior is able to provide strong social norms in analyzing data, the formation of a positive attitude in managing finances, and increased control of investors in financial results.